Antimicrobial use for treatment of healthcare-associated infections and bacterial resistance in a reference neonatal unit - Ana Carolina Bueno e Silva; Leni Márcia Anchieta; Viviane Rosado; Janita Ferreira; Wanessa Trindade Clemente; Julia Sampaio Coelho; Paulo Henrique Orlandi Mourão; Roberta Maia de Castro Romanelli (Elsevier, 2021)
Objective: The use of broad-spectrum antimicrobials, such as third and fourth-generation, are responsible for emergence of multidrug-resistant microorganisms in neonatal units. Furthermore, antimicrobial daily doses are not standardized in neonatology. This study aimed to investigate the association between the use of antimicrobial broad spectrum to bacterial sensitivity profile in a referral unit of neonatal progressive care. Methods: This is a cohort study conducted in a referral neonatal progressive care unit from January 2008 to December 2016. The data of all hospitalized neonates was collected daily. The infection criteria used were the standardized national criteria, based on definitions of Center for Diseases Control and Prevention. In this study, the use of antimicrobials was evaluated as antimicrobial-day (ATM-day) and the ratio of multidrug-resistant microorganisms per 1000 ATM-day of broad spectrum was also calculated. The study was approved by the Institutional Review Board of the Universidade Federal de Minas Gerais (ETIC 312/08 e CAAE 58973616.2.0000.5149). Results: From 2008 to 2016, 2751 neonates were hospitalized, corresponding to 60,656 patient-days. The ratio of multidrug-resistant microorganisms per 1000 ATM-day of broad spectrum was 1,3 in the first period and 4,3 in the second period (p = 0,005). Conclusion: It was observed that use of broad-spectrum antimicrobials, especially those with coverage for Gram-negative bacteria, was associated with an increase of multidrug-resistant bacteria.